Decoding the etiology of immune-mediated inflammatory diseases statistically - ElAbd, Hesham; Mahdy, Aya K. H. (Frontiers in Immunology, 2025)
Immune-mediated inflammatory diseases (IMIDs) are incurable pathologies with an increased prevalence. Whereas different risk factors for IMIDs have been identified, such as microbial dysbiosis, diet, Epstein-Barr virus infection, the exact cause of most of these diseases remains unknown and it is thought to be a combination of environmental exposures and genetic predispositions. Despite their different clinical presentation, most IMIDs are genetically associated with variants at multiple immune-related genes, predominately with different human leukocyte antigen (HLA) alleles suggesting a strong pathological involvement of adaptive immune responses. However, antigens causing these diseases remain, in most cases, unknown. Using statistical analyses of the immune repertoire, several markers of antigenic exposures have been associated with IMIDs. Here, we discuss different approaches to identify disease-associated antigenic exposure markers and formulate a framework to test their causal role in IMIDs. We then discuss the potential contribution of risk HLA alleles to diseases development and lastly, we discuss how either antigens causing IMIDs or their signatures on the immune repertoire can be exploited therapeutically.